Measuring national interests in the international coffee agreement - Roland Herrmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
This article shows how national interests in price-changing international commodity agreements can be measured. Two approaches are distinguished. Firstly, changes in national interests can be measured that are caused by the introduction of an international commodity agreement in an otherwise unregulated world market. This approach is based on a comparison of the situations with and without a commodity agreement. It represents a positive approach to measuring national interests. Secondly, changes in national interests can be measured that result from the individual country's decision to participate in the agreement or to stay outside. This approach compares the situation of participation with that of non-participation in an existing commodity agreement. As the consequences of a national decision are analyzed, it is a normative or decision-oriented approach to measuring national interests. The ICA is a particularly interesting scheme to show the two approaches, as some countries participate in the agreement while others do not. This has led to the co-existence of a controlled and an uncontrolled market with different prices.
Keywords: 330; Kaffeepolitik